Determination of Complex Formation between Drosophila Nrf2 and GATA4 Factors at Selective Chromatin Loci Demonstrates Transcription Coactivation - Emma Neidviecky; Huai Deng (Cells, 2023)
Nrf2 is the dominant cellular stress response factor that protects cells through transcriptional responses to xenobiotic and oxidative stimuli. Nrf2 malfunction is highly correlated with many human diseases, but the underlying molecular mechanisms remain to be fully uncovered. GATA4 is a conserved GATA family transcription factor that is essential for cardiac and dorsal epidermal development. Here, we describe a novel interaction between Drosophila Nrf2 and GATA4 proteins, i.e., cap‘n’collar C (CncC) and Pannier (Pnr), respectively. Using the bimolecular fluorescence complementation (BiFC) assay—a unique imaging tool for probing protein complexes in living cells—we detected CncC–Pnr complexes in the nuclei of Drosophila embryonic and salivary gland cells. Visualization of CncC–Pnr BiFC signals on the polytene chromosome revealed that CncC and Pnr tend to form complexes in euchromatic regions, with a preference for loci that are not highly occupied by CncC or Pnr alone. Most genes within these loci are activated by the CncC–Pnr BiFC, but not by individually expressed CncC or Pnr fusion proteins, indicating a novel mechanism whereby CncC and Pnr interact at specific genomic loci and coactivate genes at these loci. Finally, CncC-induced early lethality can be rescued by Pnr depletion, suggesting that CncC and Pnr function in the same genetic pathway during the early development of Drosophila. Taken together, these results elucidate a novel crosstalk between the Nrf2 xenobiotic/oxidative response factor and GATA factors in the transcriptional regulation of development. This study also demonstrates that the polytene chromosome BiFC assay is a valuable tool for mapping genes that are targeted by specific transcription factor complexes.